Pendampingan Simulasi Visitasi Akreditasi Ban S/M Melalui Konsep Pemberdayaan - Muhamad Rudi Wijaya (Yayasan Literasi Sains Indonesia, 2022)
School and madrasah accreditation is a comprehensive school/madrasah feasibility assessment process, the results of which are realized in the form of independent professional public accountability called BAN S/M. Accreditation practice can be seen from two things that are measured, namely the review of administrative compliance (compliance) and performance (performance) of the education unit for efficiency and easy and accountable implementation. The results of interviews with school principals that UPTD SD Negeri 1 Rejoagung Batanghari District, East Lampung Regency, Lampung has implemented eight National Education Standards regulating the change of the accreditation system by the National Accreditation Board (compliance) to performance-based (performance), which is emphasized on 4 main components What is assessed is the quality of graduates, the learning process, the quality of teachers, and the school/madrasah management has not been fully understood by the principal as well as education staff and education staff at UPTD SD Negeri 1 Rejoagung Batanghari District, East Lampung Regency, Lampung. Outcomes of service activities on the importance of school accreditation, understanding the flow of preparation of accreditation forms and documents. With this community service activity, it has an impact on understanding the importance of accreditation so that school awareness and responsibility will grow in ensuring the quality of quality education.